Leadership and diversity challenging theory and practice in education - Lumby, Jacky
As society becomes increasingly diverse, there is international awareness in education about how this impacts on leaders & leading. For decades the emphasis has been placed on increasing the number of leaders with specific attributes. This text takes a wider view, challenging the reader to recognise the importance of diversity issues
Keywords: Educational leadership; Diversity in the workplace; Schulleitung